Towards Malaysian common law: convergence between indigenous norms and common law methods - Farid Sufian Shuaib, (Fakulti Undang - Undang, 2009)
The predecessors of the Civil Law Act 1956, namely the various Ordinances and enactments, had served well the British imperialist in Malaya and Borneo. They provide a semblance of legitimacy to things the British had done and continue to do, namely imposing their law on the colony. They also have served well a newly independent Malaya and Malaysia in providing continuity and stability to her fragile legal system that suffered the onslaught of imperialist law and political might. The purpose of this research is to examine whether English common law should continue to dominate the development of Malaysian law. Secondly, the work seeks to examine the scheme in which the English common law methods could be employed to develop Malaysian common law. This research found that the inapt position of English law in a land rich in her own culture and heritage, and the impracticality of keeping up with the mercantile law of a foreign land, suggests a need to wean off the law of mother England. Physical judicial autonomy obtained by severance of appeal to the Judicial Committee of the Privy Council should be followed by substantive autonomy by severing the umbilical cord with English law. Malaysian common law may be developed by considering Malaysian indigenous law which refers to laws, customs and norms of the Malaysian to nurture a truly Malaysian common law. In this way, the interaction between the English legal system and the Malaysian legal system will not be a matter of domination but of convergence